2017
DOI: 10.1136/bmjopen-2017-016546
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two methods to estimate adverse events in the IBEAS Study (Ibero-American study of adverse events): cross-sectional versus retrospective cohort design

Abstract: BackgroundAdverse events (AEs) epidemiology is the first step to improve practice in the healthcare system. Usually, the preferred method used to estimate the magnitude of the problem is the retrospective cohort study design, with retrospective reviews of the medical records. However this data collection involves a sophisticated sampling plan, and a process of intensive review of sometimes very heavy and complex medical records. Cross-sectional survey is also a valid and feasible methodology to study AEs.Objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 22 publications
1
13
0
1
Order By: Relevance
“…Moderate severity AE were the most frequent (42%), followed by mild and severe AE. This is consistent with that obtained in other cross‐sectional studies, 25,35 but differs from that found in longitudinal studies, in which mild AE are usually more frequent (50%) 40,42 …”
Section: Discussionsupporting
confidence: 91%
“…Moderate severity AE were the most frequent (42%), followed by mild and severe AE. This is consistent with that obtained in other cross‐sectional studies, 25,35 but differs from that found in longitudinal studies, in which mild AE are usually more frequent (50%) 40,42 …”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, the fact that the prevalence design proportionally detects more serious AEs is not an inconvenience, as it is precisely these events that we should prioritise when analysing and establishing preventive and control strategies to reduce recurrence [28].…”
Section: Discussionmentioning
confidence: 99%
“…The methodology that ideally should be used for these types of epidemiological studies has been widely analysed, with a general consensus that it should be based on the objectives of the study and the need to combine the minimisation of bias and validity to identify AEs with reproducibility of value judgments in their iatrogenic or avoidable nature [21,28].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of in-hospital AEs in the European Union ranges from 8% to 12%, where 1 in every 100,000 inhabitants dies from this cause, i.e., about 5000 deaths per year [2,3]. The latest report by the Ibero-American Study of Adverse Events (IBEAS) established a prevalence of AEs of 10.5% and a cumulative incidence close to 20% [4]. AEs increase hospital stays by a mean of 8.7 days and double inpatient mortality (relative risk (RR) = 2.10) [5,6].…”
Section: Introductionmentioning
confidence: 99%